2011
DOI: 10.2174/1874312901105010069
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Glucosamine Sulfate in the Treatment of Osteoarthritis: Evidence of Long-Term Cardiovascular Safety from Clinical Trials

Abstract: Background and Objective:Glucosamine is a safe and common treatment for osteoarthritis. Even so, literature data on the cardiovascular safety of glucosamine are limited. The objective of this paper is to investigate the long-term effects of crystalline glucosamine sulfate (CGS) on key measures of cardiovascular risk in patients with osteoarthritis.Methods: We analyzed safety data from two long-term (6-month and 3-year, respectively) randomized controlled trials of CGS. Mean changes in blood pressure, lipids, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 42 publications
(48 reference statements)
0
10
0
3
Order By: Relevance
“…Regarding disease modification, a SR found no statistically significant differences in minimum JSN between glucosamine and placebo at 1-year follow-up, though a moderate effect was detected at 3 years 48 . A 2011 safety review found that long-term use of glucosamine was not associated with cardiovascular (CV) safety risks 54 . Two more meta-analyses found no increase in overall adverse events relative to placebo 45,52 .…”
Section: Rationalementioning
confidence: 99%
“…Regarding disease modification, a SR found no statistically significant differences in minimum JSN between glucosamine and placebo at 1-year follow-up, though a moderate effect was detected at 3 years 48 . A 2011 safety review found that long-term use of glucosamine was not associated with cardiovascular (CV) safety risks 54 . Two more meta-analyses found no increase in overall adverse events relative to placebo 45,52 .…”
Section: Rationalementioning
confidence: 99%
“…Among these, eight studies were excluded because of lack of a placebo-control (23)(24)(25)(26)(27)(28)(29)(30), two because they were not double-blinded (31,32) and one because it was not randomised (33). Six articles were ruled out as their outcomes measures were not relevant to the efficacy (34)(35)(36)(37)(38)(39), one article because of insufficient data (40), three because they were reports of other studies (41)(42)(43) and three because the intervention treatment was not glucosamine alone (44)(45)(46).…”
Section: Resultsmentioning
confidence: 99%
“…29 Two more SRs found no increase in overall adverse events when compared with placebo. 5,6 Scroggie et al, 30 in an RCT evaluating glucosamine hydrochloride side effects, concluded that oral glucosamine supplementation did not adversely affect glycemic control when administered to patients with type 2 diabetes mellitus.…”
Section: Glucosaminementioning
confidence: 94%